The relationship between the selected organizational factors and staff attraction - Nurul Hanis, Azmi (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is conducted to identify the relationship between dimension of emotional intelligence and job performance among salesperson in selected electronic store. The independent variables of this study comprise of self-awareness, self-regulations, social awareness and relationship management; whereas the dependent variable in this study is job performance. The quantitative research method is selected and questionnaire is used as the research instrument to collect data. There are 66 samples randomly selected from selected salesperson (N=80). The data collected is analyzed by using Statistical Packages for Social Science Version 22.0 (SPSS Version 22.0) software. The Spearman rho test is used to test the relationship between independent and dependent variables which is non-parametric correlations. The results revealed that there are positive relationship between job performance with self-awareness, self-regulation, social awareness and relationship management. In short, the relationship management contributes the most dominant factor to the job performance under Malaysia context. This study gives an insight to the organization in designing an appropriate system to enhance the organizational productivity.